NMC B3 Daily Northern Hemisphere Analyses for 1963 August to 1972 December - National Centers For Environmental Prediction/National Weather Service/NOAA/U.S. Department Of Commerce (UCAR/NCAR - Research Data Archive, 1980)
NMC operationally produced these daily gridded Northern Hemisphere analyses of various tropospheric levels for the period August 1963 to December 1972. Parameters include upper-level winds, surface temperature, sea-level pressure, tropopause pressure and temperature, and 500mb relative humidity on a 47 by 51 polar-stereographic grid centered on the North Pole.